Campesinato e agroecologia em rede: a dinâmica do movimento agroecológico no Brasil e sua manifestação no Nordeste e no Agreste Paraibano - Silva, Pablo Melquisedeque Souza e (2019)
This research has as main focus the analysis of the constitution of agroecological networks and their relation with Brazilian peasantry, in different scales, besides studying its fundamental relevance for the construction of agroecological knowledge as an instrument of struggle, persistence and resistance in the formation of territories of hope. In addition to the collection of secondary data and bibliographic studies related to the basic themes of this research, several field studies were carried out. Fieldwork was carried out in areas of agroecological actions: on sites, events that promoted agroecology, demonstrations at the headquarters of selected entities and at national, regional and local events related to agroecology. In this way, we seek to study the main national networks that make up the agroecological movement in Brazil, based on the Articulação Nacional de Agroecologia(ANA) (National Articulation of Agroecology). And, in view of the reflection of this integration in networks, we chose to analyze the performance of the Polo da Borborema and its partners in Agreste Paraibano, mainly the configuration of the Borborema Pole Bank Network of Community Seeds (BSCs). The trajectory of this research made it possible to understand that the network action of the agroecological movement in Brazil is a fundamental tool for strengthening, at different scales, the Brazilian peasantry. In this way, agroecology is an instrument of struggle and promotion of alternative strategies for peasantry resistance, and the network, around it, helps in the integration of subjects and organizations, collaborating with the construction of the movement, science and agroecological social practice. As we understand that the actions of ANA and ABA-agroecology were, and still are, relevant for the construction of the Brazilian agroecological movement, we believe that the Borborema's Pole action, in particular the actions of the Community Seed Bank Network, is example of the dynamics of so many agro-ecological experiences in Brazil. Therefore, the articulations and sharing of techniques and experiences that value traditional knowledge are presented as an alternative to the hegemonic, modernizing and degrading model: agribusiness. And the construction of agroecological knowledge and rationality, articulated in a network, shows itself as an alternative that strengthens the peasantry before capital and contributes to the formation of territories that are the fruit of rupture, generated on the basis of utopia and hope: the Territory of Esperança (MOREIRA and TARGINO, 2007).